International Perspectives on Motivation
XIII, 244 p.
Keywords: Bringing together motivation-related practical concerns and debates from diverse international contexts and educational settings where English is learned, this book shows how locally produced insights and issues can have wider global significance, resonating with the experiences and concerns of English teachers and learners across the world.